Morphological and photodecomposition rate constant study of PV films doped with sulfadiazine tin(IV) complexes / Salam A. Mohammed ... [et al.] - Mohammed, Salam A; Najim, Liqaa H.; Al-mashhadani, Mohammed H.; Ismael, Mustafa; Hamad, Basheer A.; Noaman, Riyadh; Ibraheem, Hanan; Ahmed, Dina S.; Yousif, Emad (Faculty of Applied Sciences, 2020)
This article focus on the calculation of photodecomposition rate constant of PVC films that containing sulfadiazine tin(IV) complexes 1-3 as photostabilzers during UV radiation exposure. This constant calculated as a method for evaluating the efficiency of sulfadiazine tin(IV) complexes 1-3 when used as a PVC photostabilizers after 300 hours of irradiation. The experimental results showed that sulfadiazine tin(IV) complexes 1-3 have reduced the rate of photodecomposition constant value of PVC films significantly with comparison to PVC (blank).